2021
DOI: 10.3390/bs11110142
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Major Depressive Disorder and Correlates of Thoughts of Death, Suicidal Behaviour, and Death by Suicide in the Geriatric Population—A General Review of Literature

Abstract: Background: There has been an increase in deaths by suicide in old age in the last decade. Depression and suicide in the elderly, 60 years and above, is a major global public health concern. Determining the prevalence of depression, and correlates of death by suicide in the geriatric population, is an important first step toward addressing this public health concern. This literature review aims to determine the prevalence of major depressive disorders and the correlates of death by suicide in the geriatric pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 106 publications
0
17
1
Order By: Relevance
“…Mood and anxiety disorders are among the leading causes of disability worldwide and place an enormous burden on society [ 1 ]. Major depressive disorder affects up to 5% of adults worldwide, leading to an increased susceptibility to a plethora of both mental and somatic diseases [ 2 ], and more importantly, an increased risk of suicide [ 3 ]. Currently used antidepressant drugs exert an effect after weeks or even months of treatment, and are not effective in so-called “treatment-resistant” depression [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mood and anxiety disorders are among the leading causes of disability worldwide and place an enormous burden on society [ 1 ]. Major depressive disorder affects up to 5% of adults worldwide, leading to an increased susceptibility to a plethora of both mental and somatic diseases [ 2 ], and more importantly, an increased risk of suicide [ 3 ]. Currently used antidepressant drugs exert an effect after weeks or even months of treatment, and are not effective in so-called “treatment-resistant” depression [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Canada, a study to assess the impact of COVID-19 among nurses showed a 5% increase in anxiety and depression from 10% to 15% pre-pandemic and early stages of the pandemic, respectively [ 15 ]. These studies demonstrate the pandemic’s psychological impact; and the need to treat any mental health condition that emerges, considering that untreated depression can be complicated with suicidal ideation, social dysfunction, and severe cognitive impairment [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proactively identifying military personnel and firefighters with risk factors for developing PTSD and offering then support and treatment can reduce future psychopathology and minimize the risk of PTSD. E-mental health services such as daily supportive text messaging can be incorporated to reduce the risk of PTSD [111][112][113][114][115][116][117][118][119][120][121].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, internet-delivered cognitive behavioral therapy may be recommended [108], and supportive text messages programs such as "Text4PTSI" and "Text4Wellbeing" can reduce mental health problems, with the former specifically reducing PTSD among first responders [109]. Various randomized controlled clinical trials have proven that supportive messaging mitigates depression, anxiety, and stress, and may mitigate PTSD [110][111][112][113][114].…”
Section: Implications For Public Policy and Practice And Future Directionsmentioning
confidence: 99%